1994
DOI: 10.1037/0022-3514.66.4.699
|View full text |Cite
|
Sign up to set email alerts
|

Self-stereotyping and social context: The effects of relative in-group size and in-group status.

Abstract: In 2 laboratory experiments, the tendency to stereotype oneself in terms of one's group membership as a function of the social context was examined. Experiment 1 examined the effects of relative in-group size on self-stereotyping. The results confirmed the prediction that minority members are more likely than majority members to stereotype themselves. Experiment 2 examined the interactive impact of relative in-group size and in-group status. As predicted, a high (relative to a low) status of the in-group incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
201
0
15

Year Published

1997
1997
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 216 publications
(225 citation statements)
references
References 18 publications
9
201
0
15
Order By: Relevance
“…Previous research has demonstrated that when the intergroup comparative context is salient perceivers self-categorize by self-stereotyping (Hogg & Turner, 1987;Simon, Glassenbayer, & Stratenwerth, 1991;Simon & Hamilton, 1994;Simon, Pantaleo, & Mummendey, 1995;Spears, Doosje, & Ellemers, 1997) assigning the same traits to the self and the ingroup (Cadinu & Rothbart, 1996;Study 1;Clement & Krueger, 2000Gramzow, Gaertner, & Sedikides, 2001;Krueger & Zeiger, 1993;Mullen, Dovidio, Johnson, & Copper, 1992;Otten, 2002, Smith, & Henry, 1996; and will tend to perceive both the ingroup and the outgroup to be more homogenous (Ellemers & van Knippenberg, 1997;Haslam, Oakes, Turner, & McGarty, 1995). Self-stereotyping is an expression of differentiation from outgroups, therefore it seems reasonable to draw a parallel here with research on behavioral contrast to outgroups.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Previous research has demonstrated that when the intergroup comparative context is salient perceivers self-categorize by self-stereotyping (Hogg & Turner, 1987;Simon, Glassenbayer, & Stratenwerth, 1991;Simon & Hamilton, 1994;Simon, Pantaleo, & Mummendey, 1995;Spears, Doosje, & Ellemers, 1997) assigning the same traits to the self and the ingroup (Cadinu & Rothbart, 1996;Study 1;Clement & Krueger, 2000Gramzow, Gaertner, & Sedikides, 2001;Krueger & Zeiger, 1993;Mullen, Dovidio, Johnson, & Copper, 1992;Otten, 2002, Smith, & Henry, 1996; and will tend to perceive both the ingroup and the outgroup to be more homogenous (Ellemers & van Knippenberg, 1997;Haslam, Oakes, Turner, & McGarty, 1995). Self-stereotyping is an expression of differentiation from outgroups, therefore it seems reasonable to draw a parallel here with research on behavioral contrast to outgroups.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Research has shown that in contrast to members of majority groups, members of minority groups are overall more cohesive, participative, cooperative and extreme, as well as more committed to enhancing their social identity and disseminating their viewpoint (e.g. Gerard, 1985;Mullen, 1991;Simon & Hamilton, 1994;Simon, Hastedt, & Aufderheide, 1997;Verkuyten, 2005; see Levine & Moreland, 1998). Interestingly, minorities seem to be less motivated to promote their claims once these are picked up and endorsed by the majority (Vernet & Butera, 2005).…”
mentioning
confidence: 99%
“…Hogg & Turner, 1987;Simon & Hamilton, 1994). De esta manera, los grupos que viven en la pobreza y que están consistentemente expuestos a ideas negativas sobre ellos podrían caer en una autoestigmatización.…”
Section: Discusión Y Conclusionesunclassified